Landscapes and artefacts : studies in East Anglian archaeology presented to Andrew Rogerson - Rogerson, Andrew; Ashley, Steven; Marsden, Adrian (Archaeopress archaeology., 2014)
Andrew Rogerson is one of the most important and influential archaeologists currently working in East Anglia. The various essays in this volume, presented to him by friends and colleagues from both the university sector and public archaeology, closely reflect his diverse interests and his activities in the region over many decades.